Actual Problems of Statistical Study of Economic Assets in Modern Conditions - V. N. Salin; M. V. Vakhrameeva; O. Y. Sitnikova (Статистика и экономика, 2020)
Purpose of research. It is necessary to clearly define the composition and structure of economic assets to conduct a systematic statistical analysis of the state and development of the national economy, including at the level of sectors, subsectors and institutional units.The purpose of the work is to systematize data on the availability and movement of economic assets in the context of information sources, methods of their assessment and analysis of the practice of macroeconomic calculations.Materials and methods. In this paper, the authors considered the classification of economic assets, applied structural and dynamic data analysis, as well as methods of theoretical research in the form of generalization, comparison, and special analytical procedures.Results. Statistical study of economic transactions with assets involves a detailed review of the groupings and classifications of assets at the level of institutional units, sectors of the economy and the economy as a whole, which will provide reliable information about their availability and movement. In addition, it is necessary to understand the essence of statistical indicators that reflect the state and change in the value of assets, the methodology for their calculation, comprehensive analysis and practical use. The paper defines the main directions for studying economic assets based on current international standards, taking into account national statistical practice.Conclusion. As part of a systematic statistical analysis of the state and development of the national economy in various areas, it is necessary to clearly define the composition and structure of economic assets, their place and significance in the production of goods and services.The issue of assessing the value of economic assets, which should reflect their market value, is of significant importance. Improving methods for assessing economic assets is an urgent problem not only for macroeconomic calculations, but also for adequately reflecting economic operations at the level of institutional units and sectors of the economy.Economic assets are recognized as such if they bring economic benefits to their owner. Evaluating the effectiveness of asset use in economic activities or asset ownership is no less challenging for analysts. Such analytical procedures require a comprehensive analysis of data on the availability and movement of assets, their composition and structure, including from an international perspective.The authors of the article have repeatedly addressed the issues of macroeconomic calculations in their publications, which allowed them to consider in more detail topical issues related to the accumulation of non-financial and financial assets.